Baroque Modernity : An Aesthetics of Theater - Cermatori, Joseph, 1983- (Book collections on Project MUSE., 2021)
Baroque Modernity will appeal to readers in a wide array of disciplines, including comparative literature, theater and performance, art and music history, intellectual history, and aesthetic theory.